Causal effects of autoimmune diseases on thyroid cancer: a two-sample Mendelian randomization study - Peng, Wenfang; Xu, Bojin; Zhou, Haiping; Du, Juan; Ge, Xiaoxu; Huang, Shan (Frontiers in Endocrinology, 2024)
Background: Although numerous studies had revealed associations between autoimmune diseases (AIDs) and thyroid cancer (TC), the potential causal associations between the two remain poorly defined.Methods: Using five approaches, two-sample Mendelian randomization (MR) analyses were carried out to determine the causal effects of 12 major AIDs on risk of TC. The sensitivity analyses were conducted to verify the reliability of the analysis. The reverse MR analysis was performed to evaluate the possibility of reverse causation.The results showed a significant causal association of systemic lupus erythematosus (SLE) and primary biliary cirrhosis (PBC) on the risk of TC. Genetically predicted PBC elevated the risk of TC (OR = 1.46, 95% CI = 1.06-2.02, p = 0.021). The risk of TC was also increased by genetically predicted SLE (OR = 6.52, 95% CI = 1.38-30.84, p = 0.018) with heterogeneity. After outlier-corrected analyses, the results still suggested that genetically predicted SLE increased the risk of TC (p = 0.019). No evidence of a causal relationship between the remaining 10 AIDs and TC was observed. No reverse causal effects of TC on AIDs were found in reverse MR analysis.These findings support a significant causal association of SLE/PBC on the increased risk of TC, indicating that patients with SLE/PBC should be under a close monitoring of TC.